Determinants of multiple agricultural technology adoption: evidence from rural Amhara region, Ethiopia - Mesele Belay Zegeye; Abebaw Hailu Fikire; Getamesay Bekele Meshesha (Cogent Economics & Finance, 2022)
The adoption of modern agricultural technologies remains to be a promising strategy to improve agricultural productivity, achieve food security and reduce poverty in Ethiopia. Despite the efforts to promote adoption in the country, the adoption rate has always been very low. So, it is essential to understand the determinants to the adoption of modern agricultural technologies. This study investigates the determinants of agricultural technology adoption decisions in the rural Amhara region of Ethiopia. The study is based on an Ethiopian socio-economic survey of 2015/16 and a sample of 656 farm households is considered. The paper uses a multinomial logit model to assess the factors affecting the adoption decision of agricultural technology. The result shows that farmers with more educational level, family size, off-farm participation, livestock, extension service, credit access, advisory service, and farmers closer to plot, all-weather road, zonal town, and farmers with lower remittance income are more likely to adopt new or improved agricultural technology. Accordingly, the study provides crucial policy implications regarding the technology adoption in the agricultural sector for all regions of Ethiopia.
Keywords: 330; Agriculture; technology adoption; multinomial logit; poverty; Ethiopia